A ausência da solidariedade na sociedade excludente e sua contribuição para a expansão do Direito Penal - Ferreira, Ana Flávia Gonzalez (2020)
The excluding society is a society developed in post-modernity, especially after the 1970s. It presents some inherent elements, as the expansion of neoliberalism, the rise of individualism, which results in a conflict in solidarity relations, particularly with the deviant "other", and the rise of mass incarceration, due to "Law and Order" and "War on Drugs" policies. We observed that the excluding society aims to divide the world into two parts: those who have conditions to pay for their eccentricity and for this reason they can be free, and those who cannot pay for their lifestyle and, therefore, end up segregated. Critical criminology, highlighting the following authors Loïc Wacquant (2015), Jock Young (2015, David Garland (2014), and Lola Anyar de Castro (2005), indicates that, with the purpose of hiding anti-grassroots policies, the electoral race starts to focus on the fear that deviant people represent. Thereby, it uses extremely punitive policies, intensifying the population’s desire for revenge against those who committed a crime. An important acknowledgment is that the incarcerated population is not random. Poor people and especially black people will be the ones imprisoned in both Central and Latin-American countries. Hence, incarceration presents not only social class but also skin color. Since the rise of individualism results in conflicts in solidarity relations, the study addresses this issue, questioning concepts such as solidarity, using for this matter, legal and sociological education. Therefore, the objectives of this work were to: 1º) analyze what an excluding society consists of in both central and peripheral countries; 2º) analyze the relationship between the rise of individualism and its impacts in solidarity; 3º) analyze how the excluding society, the rise of individualism and the lack of solidarity affect the expansion of criminal law. A bibliographic review was used as a research method. This work is justified because excluding society is in progress, leaving a large number of people incarcerated all over the world